Effect of Partial Solution Treatment Temperature on Microstructure and Tensile Properties of 440C Martensitic Stainless Steel - Junaidi Syarif; Mohammad H. Yousuf; Zainuddin Sajuri; Amir Hossein Baghdadi; Mahdi Merabtene; Mohd Zaidi Omar (Metals, 2020)
The 440C martensitic stainless steel is considered to be among the hardest steels, owing to its high carbon content. Careful heat treatment of this material introduces multiple carbide particles, which can alter microstructure and mechanical properties. This study focused on the effect of austenitisation temperature on the microstructure and tensile properties of 440C steel. Austenitisation was performed on the austenite + carbide region, because 440C steel lacks a single-phase region. The steel was austenitised at two different temperatures; namely, 1160 °C and 950 °C, and subjected to oil quenching. The as-quenched samples showed a typical lath martensite structure with retained austenite phase. The treatments at 1160 °C and 950 °C promoted the formation of M7C3 and M23C6 carbides, respectively. The austenite grains in the sample treated at 1160 °C showed a higher growth rate than those in the sample treated at 950 °C. The sample treated at 1160 °C showed low-fraction and a large-size carbide phase. The Zener pinning force decreased, thereby increasing the austenite grain growth in the sample treated at 1160 °C. The hardness and 0.2% proof stress of the sample treated at 950 °C were higher than those of the sample treated at 1160 °C, owing to the higher martensite content in the former. The strength–ductility balance of the sample treated at 950 °C was higher than that of the sample treated at 1160 °C. The decreased austenitisation temperature resulted in improved mechanical properties of the steel. Therefore, the austenitisation temperature alters the microstructure and mechanical properties of 440C steel.